My Barrel Chair: Evoking the Past, Prophesying Armageddon - Maynard, Lara (Ethnologies, 1999)
This paper explores how an artifact (barrel chair) is correlative of memory by considering its historical context and the cluster of informants’ narratives and comments, which include bits of biography and autobiography, prompted by the chair as a visual mnemonic device. The chair is shown to be evocative of a bygone era for the septuagenarian informants, who express a cohort awareness, and also a stimulus for conversation about the present and future. Hence, the single artifact is mnemonic, contemporary and prophetic.